Factors Influencing the Implementation of the Hospital Management Information System on the Quality of Service - Zebua, Markus Sastra Eli; Amirah, Asriwati; Harahap, Juliandi (Newinera Publisher, 2024)
An information system serves as a formal mechanism that supplies management with precise and timely data essential for decision-making, facilitating successful planning, oversight, and operational functions. This research employs a quantitative methodology with a cross-sectional design. The research population comprises employees utilizing computer systems in units linked to SIiMRS, with a sample size of 125 individuals. This research indicates that human resources significantly influence the implementation of SIMRS on service quality at RSU Bethesda Gunungsitoli, with a p-value of 0.000, which is less than 0.05. The hardware significantly influences the implementation of SIMRS on service quality at RSU Bethesda Gunungsitoli, evidenced by a p-value of 0.001, which is less than 0.05. The implementation of software in SIMRS affects the quality of service at RSU Bethesda Gunungsitoli, evidenced by a p-value of 0.014, which is less than 0.05. Data management significantly influences the implementation of SIMRS on service quality at RSU Bethesda Gunungsitoli, evidenced by a p-value of 0.035, which is less than 0.05. The LAN conditions significantly influence the implementation of SIMRS on the quality of service at RSU Bethesda Gunungsitoli, evidenced by a p-value of 0.023, which is less than 0.05. The findings of the multivariate analysis indicated that human resource factors exerted the most significant impact on service quality at RSU Bethesda Gunungsitoli. The continuity variable is indicated as 7.807, signifying that respondents with proficient human resources possess a 7.807 likelihood of enhancing the quality of service at RSU Bethesda Gunungsitoli.